INFLATION AND ITS IMPACT ON THE STANDARD OF LIVING OF THE POPULATION - Dilmuradov , Shaxboz (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the impact of inflation on the living standards of the population. The main causes of inflation, including demand and supply factors as well as internal and external economic conditions, are examined. The study highlights the effects of inflation on society, such as a decrease in real income, depreciation of savings, and an increase in social inequality. In addition, effective measures to control inflation, including monetary policy and social protection mechanisms, are proposed.